Thermophysical properties of the products of low-grade fuels thermal recycling; MATEC Web of Conferences; Vol. 23 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment - Tabakaev R. B. Roman Borisovich; Astafyev A. V. Aleksandr Vladimirovich; Kazakov A. V. Aleksandr Vladimirovich; Zavorin A. S. Aleksandr Sergeevich (2015, 2015)
Title screen